The boxer-trainer, actor-director relationship: an exploration of creative freedom - Lennox, P. S.; Rodosthenous, G. (Sport in Society: Cultures, Commerce, Media, Politics, 2016)
The similarities between the way performance knowledge is transmitted for martial and theatrical artists have been examined by Phillip Zarrilli. Zarrilli argues that strips of codified behaviour present artists with restricted fields of choice, a precise vocabulary of techniques and strictly prescribed parameters within which to operate. We extend this argument to include combat athletes, particularly boxers, proposing a closer examination of choice, agency and creative freedom within the boxer-trainer and actor-director relationship. Drawing upon autoethnographic data, and participant interviews, we explore how trainers, boxers, directors and actors talk about creative freedom as it relates to their relationships. This co-authored article uses two discrete voices to explore this creative freedom: P. Solomon Lennox writes from a boxer`s perspective and George Rodosthenous from a director`s point of view.